Improved survival of hospitalized patients with cardiac arrest due to coronary heart disease after implementation of post-cardiac arrest care: A population-based study. Issue 37 (September 2018) - Lin, Yu; Tsai, Shih-Hung; Yang, Chen-Shu; Wu, Chun-Hsien; Huang, Chih-Han; Lin, Fu-Huang; Ku, Chih-Hung; Chung, Chi-Hsiang; Chien, Wu-Chien; Lai, Chung-Yu; Chu, Chi-Ming
Abstract : Abstract: Post-cardiac arrest care was implemented in 2010 and has been shown to improve the survival of patients with coronary heart disease (CHD). However, the findings varied for different survival conditions. We conducted a retrospective longitudinal study of records from 2007 to 2013 in the National Health Insurance Research Database. We evaluated the differences in short-term (2-day and 7-day) and long-term (30-day and survival to discharge) survival after the implementation of post-cardiac arrest care and among age subgroups. We reviewed inpatient datasets in accordance with the International Classification of Disease Clinical Modification, 9th revision codes (ICD-9-CM). Eligible participants were identified as those with simultaneous diagnoses of cardiac arrest (ICD-9-CM codes: 427.41 or 427.5) and CHD (ICD-9-CM codes: 410–414). Multiple logistic regression was applied to establish the relationship between calendar year and survival outcomes. The odds of 2-day survival from 2011 to 2013 were higher than those from 2007 to 2010 (adjusted odds ratio [aOR]: 1.15; 95% confidence interval [CI]: 1.03–1.29). Similarly, the odds of 7-day survival from 2011 to 2013 were higher than those from 2007 to 2010 (aOR: 1.11; 95% CI: 1.01–1.22). Improvements in the odds of 2-day and 7-day survival were discovered only in patients <65 years old. Our data reinforce that short-term survival improved after implementation of post-cardiac arrest care. However, older age seemed to nullify the influence of post-cardiac arrest care on survival.